Mechanisms of Pharmaceutical Therapy and Drug Resistance in Esophageal Cancer - Mao, Chengyi; Zeng, Xiaoxi; Zhang, Chao; Yang, Yushang; Xiao, Xin; Luan, Siyuan; Zhang, Yonggang; Yuan, Yong (Frontiers in Cell and Developmental Biology, 2021)
Pharmaceutical therapies are essential for esophageal cancer. For the advanced esophageal cancer, the neoadjuvant therapy regimen, including chemotherapy plus radiotherapy and/or immunotherapy is effective to achieve clinical benefit, even pathological complete response. For the unresectable, recurrent and metastatic esophageal cancer, the pharmaceutical therapy is the limited effective regimen to alleviate the disease and prolong the progression-free survival and overall survival. In this review, we focus on the pharmaceutical applications in esophageal cancer treatment including cytotoxic agents, molecular targeted antibodies, and immune checkpoint inhibitors. The chemotherapy regimen is based on cytotoxic agents such as platinum-based complexes, fluorinated pyrimidines and taxenes. Although the cytotoxic agents have been developed in past decades, the standard chemotherapy regimen is still the cisplatin and 5-FU or paclitaxel because the derived drugs have no significant advantages of overcoming the shortcoming of side effects and drug resistance. The targeted molecular therapy is an essential supplement for chemotherapy; however, there are only a few targeted therapies available in clinical practice. Trastuzumab and ramucirumab are only two molecular therapy drugs which approved by the US Food and Drug Administration to treatment advanced and/or metastatic esophageal cancer. Although the targeted therapy usually achieves effectiveness benefit in the early-stage therapy of esophageal cancer, the patients will always develop drug resistance during treatment. Immune checkpoint inhibitors have a significant impacted on routine clinical practice in cancer treatment. The anti-programmed cell death-1 monoclonal antibodies pembrolizumab and nivolumab, as the immune checkpoint inhibitors, are recommended for advanced esophageal cancer by several clinical trials. However, the significant issues of pharmaceutical treatment are still the dose-limiting side effects and primary or secondary drug resistance. These defects of pharmaceutical therapy restrain the clinical application and diminish the effectiveness of treatment.